2021
DOI: 10.1186/s13722-021-00247-5
|View full text |Cite
|
Sign up to set email alerts
|

What do clinicians want? Understanding frontline addiction treatment clinicians’ preferences and priorities to improve the design of measurement-based care technology

Abstract: Background Measurement-based care (MBC) is the practice of routinely administering standardized measures to support clinical decision-making and monitor treatment progress. Despite evidence of its effectiveness, MBC is rarely adopted in routine substance use disorder (SUD) treatment settings and little is known about the factors that may improve its adoptability in these settings. The current study gathered qualitative data from SUD treatment clinicians about their perceptions of MBC, the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Despite numerous potential barriers, the current pilot study found that digital, remotely delivered MBC was feasible to incorporate into SUD treatment as usual with high rates of engagement and high ratings of usability and clinical utility reported by patients and clinicians. It is possible that the positive findings obtained here are partly attributable to the user-centered design methods that informed the specific designs, workflows, and contents included in the MBC system that was piloted in the current study ( 8 , 10 ). For example, informed by stakeholder input, we designed the MBC system to allow patients to complete weekly check-ins on their personal smartphones (in contrast to our initial idea of using tablet computers or paper questionnaires in clinic waiting rooms), which may address some implementation barriers cited above by integrating the weekly check-in with existing technologies used by patients and by eliminating the need for clinicians to administer and score MBC measures.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Despite numerous potential barriers, the current pilot study found that digital, remotely delivered MBC was feasible to incorporate into SUD treatment as usual with high rates of engagement and high ratings of usability and clinical utility reported by patients and clinicians. It is possible that the positive findings obtained here are partly attributable to the user-centered design methods that informed the specific designs, workflows, and contents included in the MBC system that was piloted in the current study ( 8 , 10 ). For example, informed by stakeholder input, we designed the MBC system to allow patients to complete weekly check-ins on their personal smartphones (in contrast to our initial idea of using tablet computers or paper questionnaires in clinic waiting rooms), which may address some implementation barriers cited above by integrating the weekly check-in with existing technologies used by patients and by eliminating the need for clinicians to administer and score MBC measures.…”
Section: Discussionmentioning
confidence: 98%
“…While SUD treatment providers have been previously shown to report positive attitudes toward MBC ( 8 , 23 ), studies have also identified numerous barriers that can impede the implementation of MBC in SUD treatment settings ( 5 , 23 25 ). Notably, implementation barriers may vary between different SUD treatment settings and may be associated with patient-, provider-, and system-level factors ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations